Assessment of ECMWF subseasonal temperature predictions for an anomalously cold week followed by an anomalously warm week in central and Southeastern South America during July 2017 - Alvarez, Mariano Sebastián (2020)
The demand of subseasonal predictions (from one to about four weeks in advance) has been consid-erably increasing as these predictions can potentially help prepare for the occurrence of high-impact events such as heat or cold waves that affect both social and economic activities. This study aims to assess the subseasonal temperature prediction quality of the European Centre for Medium-Range Weather Forecasts (ECMWF) against the Japan Meteorological Agency reanalyses. Two consecutive weeks of July 2017 were analyzed, which presented anomalously cold and warm conditions over central South America. The quality of 20 years of hindcasts for the two investigated weeks was compared to that for similar weeks during the JJA season and of 3 years of real-time forecasts for the same season. Anomalously cold temperatures observed during the week of 17–23 July 2017 were well predicted one week in advance. Moreover, the warm anomalies observed during the following week of 24–30 July 2017 were well predicted two weeks in advance. Higher linear association and discrimination (ability to distinguish events from nonevents), but reduced reliability, was found for the 20 years of hindcasts for the target week than for the hindcasts produced for all of the JJA season. In addition, the real-time forecasts showed generally better performance over some regions of South America than the hindcasts. The assessment provides robust evidence about temperature prediction quality to build confidence in regional subseasonal forecasts as well as to identify regions in which the predictions have better performance.